Flight mechanics modeling and analysis - Raol, Jitendra R. 1947-; Singh, Jatinder 1964- (CRC Press, Taylor & Francis Group, 2023)
Cover -- Half Title -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- Preface -- Acknowledgements -- Authors -- Introduction -- I.1 Modeling -- I.2 Flight Simulation -- I.3 Flight Control -- I.4 Artificial Neural Networks (ANNs) in Control -- I.5 Fuzzy Logic-Based Control -- I.6 Evaluation of Aircraft Control-Pilot Interactions -- I.7 Chapter Highlights -- References -- Chapter 1 Aerodynamic Principles and Fundamentals -- 1.1 Aerodynamic Concepts and Relationships -- 1.1.1 Air Pressure -- 1.1.2 Air Density -- 1.1.3 Air Temperature -- 1.1.4 Altitudes -- 1.1.5 Airspeeds-IAS, CAS, EAS, TAS -- 1.1.6 Bernoulli's Continuity Equations -- 1.1.7 Mach Number -- 1.1.8 Reynold's Number -- 1.1.9 Viscosity -- 1.2 Aircraft Force Parameters -- 1.2.1 Lift -- 1.2.2 Weight -- 1.2.3 Thrust -- 1.2.4 Drag -- 1.2.5 Load Factor -- 1.2.6 Drag Polars -- 1.3 Aerodynamic Derivatives - Preliminary Determination -- 1.4 Aircraft Propulsion and Its Performance -- 1.5 Aircraft Sensors-Instrumentation Systems -- 1.5.1 Air-Data Instruments -- 1.5.2 Pressure Altimeter -- 1.5.3 Air Speed Indicator -- 1.5.4 Mach Meter -- 1.5.5 Vertical Speed Indicator -- 1.5.6 Accelerometers -- 1.6 Energy Awareness, Convergence, and Management -- 1.7 Angle of Attack Awareness and Management -- Appendix 1A Airflow -- 1A.1 Boundary Layer -- Appendix 1B Aircraft Engines -- 1B.1 Engine Thrust Computations -- 1B.2 For Turbojet-Type Engine -- Epilogue -- References -- Chapter 2 Engineering Dynamics -- 2.1 Introduction -- 2.2 Kinematics -- 2.2.1 Rectangular Cartesian Coordinates -- 2.2.2 Curvilinear Coordinates -- 2.3 Relative Motion -- 2.3.1 Displacement and Time Derivatives -- 2.3.2 Angular Velocity and Acceleration -- 2.3.3 Velocity and Acceleration Using a Moving Reference Frame -- 2.4 Kinematics of Constraint Rigid Bodies -- 2.4.1 General Equations -- 2.4.2 Eulerian Angles.
Keywords: Flugmechanik; Numerisches Modell; Flight control-Simulation methods; Aerodynamics-Mathematics; Airplanes-Control systems-Mathematical models; Electronic books